Autonomy, the Right Not to Know, and the Right to Know Personal Research Results: What Rights Are There, and Who Should Decide about Exceptions?. Issue 1 (28th April 2014) - Helgesson, Gert
Abstract : This paper defends the right not to know personal health information, while it discards the right of research participants to receive individual research results. Disagreement regarding the right not to know stems from two different conceptions of autonomy, leading to opposing normative conclusions. Researchers occasionally have good reason to inform research participants about incidental findings in spite of the absence of a right to know such information. Such decisions have to be made by health care personnel and researchers on a case by case basis, although external support for the decisions may be available.